First language attrition - Ісаєва, Є. О. (НТУ ДП, 2024)
Firstly, it's crucial to understand how babies learn a language. Aditi Thombre explains that even before birth, they can differentiate around 800 sounds! The brains of newborns are primed to grasp language. While children may not form grammatically correct sentences initially, this falls within the critical period, which spans from infancy to pre-teen years. The process of language acquisition varies slightly for those exposed to a completely new language.
Keywords: language attrition